FRI0334 Comparative Effectiveness of Rituximab versus Subsequent Anti-Tumor Necrosis Factor in Cumulative Prednisone Exposure in Patients with Rheumatoid Arthritis with Prior Exposure to Tnfi. (10th June 2014) - Harrold, L.; Reed, G.; Magner, R.; Shewade, A.; John, A.; Greenberg, J.; Kremer, J.
Abstract : Background: In a US cohort of RA patients (pts) with prior exposure to 1 or more TNF inhibitors (TNFi), use of rituximab (RTX) was associated with a higher likelihood of low disease activity or remission (based on Clinical Disease Activity Index [CDAI] ≤10) as compared with a subsequent TNFi. 1, 2 However, it is not known whether the increased efficacy was due to greater use of prednisone. Objectives: To examine the comparative effectiveness of RTX vs a subsequent TNFi in terms of cumulative prednisone exposure in RA pts with prior TNFi exposure using data from the Consortium of Rheumatology Researchers of North America (CORRONA), a multi-center observational registry within the US. Methods: Using CORRONA data spanning from 2/28/2006 through 10/31/2012, we identified RTX-naïve RA pts with prior TNFi use who were initiating RTX or a subsequent TNFi, had a 1-year follow-up visit and had CDAI measurements at baseline and 1-year follow-up. Pts from the stratified-matched cohort of the previously described comparative effectiveness analysis were assessed in the current analysis. 1, 2 A propensity score for TNFi vs RTX was estimated using baseline clinical characteristics with matching of pts stratified based on 1 vs ≥2 prior TNFi use. The primary outcome was area under the curve (AUC) for cumulative prednisone dose divided by time. The percentage of time spent at 10mg or higher of prednisone was examined as a secondary outcome. Multivariable linear mixed models were performed adjusting for age, gender, 1 vs ≥2 prior TNFi, baseline CDAI, baseline prednisone use and baseline methotrexate use. Results: There were 205 RTX pts and 205 TNFi matched pts who met the inclusion criteria. Patients were mostly female (81-83%), with a mean age of 58, mean disease duration of 15 years, and mean CDAI of 26-27. Baseline prednisone was used in 55.6% of RTX users and 51.5% of TNFi users. Overall there was a significant decrease in cumulative prednisone use over time ( P =0.04). The mean AUC for RTX was 3.7 vs 3.2 for TNFi ( P =0.22). In adjusted models, the mean difference in AUC over time for RTX as compared with TNFi was 0.26 (95% CI: -0.29, 0.82). The mean percentage of time at prednisone dose ≥10mg was 15.0% in RTX users vs 11.3% in TNFi users ( P =0.21). With adjustment for confounders, the mean difference in the percentage of time at prednisone dose ≥10mg for RTX compared with TNFi was 2.79 (95% CI: -2.45, 8.03). Approximately 14.0% and 22.9% of RTX and TNFi baseline prednisone users, respectively, discontinued prednisone during follow-up. Conclusions: In this population of RA pts with prior exposure to TNFi, treatment with RTX was associated with a higher likelihood of achieving low disease activity and remission (OR 1.54, 95% CI 1.01-2.35) compared with subsequent TNFi users 1, 2 and it was not related to greater prednisone use. Both RTX and TNFi users had a reduction in cumulative prednisone use. References: Harrold LH, et al. Arthritis Rheum. 2013;65(suppl 10) [abstract 1438]. Harrold LH, et al. Ann Rheum Dis. 2013;72(suppl 3) [abstract 460]. Acknowledgements: This study is sponsored by CORRONA. In the last 2 years, AbbVie, Amgen, AstraZeneca, Genentech, Horizon Pharma, Eli Lilly, Novartis, Pfizer, Vertex, and UCB have supported CORRONA through contracted subscriptions. Disclosure of Interest: L. Harrold Grant/research support: CORRONA., G. Reed Employee of: CORRONA, Inc., R. Magner Employee of: University of Massachusetts., A. Shewade Employee of: Genentech, Inc., A. John Employee of: Genentech, Inc., J. Greenberg Shareholder of: CORRONA., Consultant for: AstraZeneca, Pfizer., Employee of: CORRONA., J. Kremer Shareholder of: CORRONA., Employee of: CORRONA. DOI: 10.1136/annrheumdis-2014-eular.1534